Adaptation Potential Evaluation of Ornamental Motifs in Huizhou Heritage Buildings under Contemporary Context: An AHP-Fuzzy Comprehensive Evaluation Model Approach - He, You; Bin Mamat, Mohd Jaki; Sun, Li (Data and Metadata, 2025)
The ornamental motifs in the structural elements of traditional Huizhou dwellings, listed as a World Heritage Site, embody the convergence of Confucian philosophy and geomantic principles. They integrated into wooden, stone, and brick carvings, reflect the local populace’s aspirations for prosperity, longevity, and familial harmony, possessing important inheritance significance. This study aims to establish a model to evaluate the adaptation potential of ornamental motifs under contemporary context in traditional Huizhou dwellings by investigating their development history, categories, and cultural meanings. This model quantifies the factors influencing the adaptation potential of these ornamental motifs, calculates the weight of each factor. The analysis results indicate that, among all the factors, the most important primary indicator is cultural connotation (0,3118). The secondary indicators are visual appeal (0.2300), compatibility with modern aesthetic needs (0.0988) and noble, elegant (0.0836). Additionally, the overall grade of adaptation potential was determined by scoring and ranking motif samples based on the fuzzy comprehensive evaluation method. This approach enhances the objectivity, scientific rigor, and accuracy of the selection of ornamental motifs, which not only provides theoretical support and practical guidance for the sustainable development of Huizhou cultural symbols, but also serves methodological reference for related fields in other countries and regions.